Factors for Ensuring the Effectiveness of Education Based on the Performance of Choral Works on the Basis of Students of Music Education in Higher Education - Khodjayev Khushnudbek Abidinovich (International Journal on Orange Technologies, 2021)
At present, the major musicologists and professors of the country are studying the problems of educating and preserving children's voices. These scientists examined the structure and developmental characteristics of the sound apparatus and proposed several scientifically based methods of nurturing and preserving children’s voices. In this article, the author discusses the factors that ensure the effectiveness of education based on the performance of choral works on the basis of students of higher education music education.